Effectiveness of High-Altitude Environments on Cardiovascular Ability: A Literature Review - Amelia Gusfiani; Wilda Welis; Anton Komaini; Zulbahri Zulbahri; Dally Rahman; Fiky Zarya (Postgraduate, University of Mataram, 2023)
The problem is a lack of a deep understanding of how living at high altitudes affects cardiovascular ability significantly. The purpose of the study was to analyze the effectiveness of living at high altitudes on improving cardiovascular ability based on a systematic literature review. This review includes an analysis of the results of the study which includes improved oxygen transport, physiological adaptation, and long-term effects on heart and vascular health. The results of this review provide insight into the potential benefits and relevance of living at high altitudes in the context of improving cardiovascular health, as well as its implications in the field of sport and public health. The methodology used is a systematic literature review that collects and analyzes the existing literature on the effects of living at a high altitude on cardiovascular ability. The result is that Living in a highland place has been proven to increase immunity. This is due to physiological adaptations that occur in response to environments with lower oxygen content. These adaptations include an increase in the number of red blood cells and oxygen transport capacity in the body, which in turn improves aerobic ability and cardiovascular endurance. Studies show that long-term exposure to high altitudes can result in improved athletic performance and cardiovascular ability in individuals who live or train at these altitudes. The conclusions of this study suggest that living at high altitudes can improve cardiovascular ability through significant physiological adaptations